Handbook of death & dying - Bryant, Clifton D., 1932- (Thousand Oaks, Calif. : Sage Publications, 2003)
"More than 100 scholars contributed to this carefully researched, well-organized, informative, and multi-disciplinary source on death studies. Volume 1, "The Presence of Death," examines the cultural, historical, and societal frameworks of death, such as the universal fear of death, spirituality and varioius religions, the legal definition of death, suicide, and capital punishment. Volume 2, "The Response to Death," covers such topics as rites and ceremonies, grief and bereavement, and legal matters after death."--"The Top 20 Reference Titles of the Year," American Libraries, May 2004.
"A Sage reference publication."
Ηλεκτρονικό βιβλίο
Keywords: Death -- Social aspects; Thanatology